The ECSIT Mediated Toll3-Dorsal-ALFs Pathway Inhibits Bacterial Amplification in Kuruma Shrimp - Ding, Ding; Sun, Xue-jun; Yan, Meng; Chen, Qi; Gao, Lin; Kang, Cui-jie (Frontiers in Immunology, 2022)
The Toll signaling pathway plays an important role in animal innate immunity. However, its activation and signal transmission greatly differ across species and need to be investigated. Shrimp farming is a worldwide economic activity affected by bacterial disease from the 1990’s, which promoted research on shrimp immunity. In this study, we first proved that, among the three identified Toll receptors in Marsupenaeus japonicus kuruma shrimp, Toll 3 plays a pivotal role in initiating the antibacterial response in vivo, especially upon anti-Staphylococcus aureus infection. Further research showed that this result was due to the activation of the Dorsal transcription factor, which induced the expression of two anti-lipopolysaccharide factors (Alfs). Moreover, the evolutionarily conserved signaling intermediate in Toll pathways, ECSIT, was proved to be needed for signal transmission from Toll 3 to Dorsal and the expression of anti-lipopolysaccharide factors. Finally, the mortality assay showed that a Toll3-ECSIT-Dorsal-Alf axis was functional in the anti-S.aureus immunity of M. japonicus shrimp. The results provide new insights into the function and signal transduction of the Toll pathway in aquatic species and offer basic knowledge for shrimp disease control and genetic breeding.